THE EFFECT OF GIVING CARROT JUICE ON DECREASING DEGREES OF DYMENORROA IN ADOLESCENT WOMENINSMP ISLAM AMANAH UMMAH MOJOLABAN - Lis Della Anggraini Saputri; Enny Yuliaswati (Universitas STRADA Indonesia, 2023)
background : During menstruation, most women experience pain in the lower abdomen, which is known as dysmenorrhea. One way to reduce dysmenorrhea is by consuming carrot juice. The purpose of this study was to determine the effect of carrot juice to reduce the degree of dysmenorrhea in young women Method :This type of research is pre-experiment with one group pre-test post-test design. Results :Before being given the intervention, the majority of respondents experienced moderate pain, then after being given the intervention, the majority of respondents experienced a decrease in pain in mild pain Analysis :The results of the analysis are knownSig.(2-tailed) value of 0.000 <(0.05) which means that there is an effect of giving carrot juice to reduce the degree of dysmenorrhea in young women. Conclusion:There is an effect of giving carrot juice to a decrease in the degree of dysmenorrhea in young women